Coventry Patmore’s Journalism: The Interface between Conservative Politics and Social Justice - Scholl, Lesa (Australasian Journal of Victorian Studies, 2020)
Critical work on Coventry Patmore has tended to see him through the lens of his perceived misogyny. Although recent scholarship has sought to recover him in a different light, his political journalism remains almost entirely neglected. This essay examines the way in which Patmore’s journalism challenges the complacency of late-Victorian conservative politics from a conservative perspective, asserting a vision of social justice that is predicated on the individual’s responsibility toward their community. This social vision in response to the failure of institutionalised social reforms owes much to Patmore’s original adherence to Tractarian values.